ENDÜSTRİ 4.0'DAN EĞİTİM 4.0'A DEĞİŞEN EĞİTİMÖĞRETİM PARADİGMALARI. - DEMİR, Abdullah (Electronic Turkish Studies)
Nowadays, many signs especially existing approximately 5.47 billion search on google per day and amount of data which stored in 2008 being more than data which have been stored for 5000 years and being produced 90 % data of world in last 2 years and companies' attempts to make volume of information double in each year are showing to go out of conventional educational approaches. Main point in the topic is noticing the necessity to new idea, education and production forms. Education is not only giving some basic information/knowledge and indoctrinating, it is also a complementary process which includes training mental ability to consider, puzzles one brain. At the present time, education also includes design, production, writing computer programs in other words coding. Economy, information and communication technologies have brought the process to new different dimensions with the power of internet. Industrial 4.0 is one result of this process and it fundamentally aims to pair up informational technologies and industrial process so there is necessity to new education system (which means education 4.0) for supplying the needs of industrial 4.0. Education 4.0 is being reached step by step from experience with memorization (Education 1.0) to internet-enabled learning (Education 2.0), from this process to consuming & producing knowledge (Education 3.0) and then to empowering education to produce innovation (Education 4.0). There are many reflections of industrial 4.0 such as peoples or organizations which has improved capabilities to think at high level education, utilizing digital technology, using individualized data and open sources, having global networks, meeting the needs of technological world, producing and transferring information. A new education system which promotes continuous learning, helps taking powerful role in community and making differences must be given to individuals. New educational technologies such as virtual reality, i-cloud, interactive books, videos and animation are supported with new non-spatial, time independent educational approaches such as informal educational programs (Khan Academy). One of the most important complementary part of education 4.0 is undoubtedly teacher. In this system teacher is not a conventional teacher. She/He is not only a person who gives information, she/he is also a person who tries to upskill students, gives common sprits and doesn't have boundaries. In this study, how education and training system editing to give answer to industrial 4.0 necessities will be examined. At the same time, there will be an evaluation of our countries current situation by revealing principles of this study.